Teknik SIT Berbantuan Aplikasi Instagram Untuk Mereduksi Strees Mahasiswa Tingkat Akhir - Suryati, Suryati; Bela Janare Putra; Hafsah Divayanti (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2024)
ABSTRACT: This research explores the effectiveness of the Stress Inoculation Training (SIT) technique, assisted by Instagram Reels, in reducing stress levels among students completing their thesis at UIN Raden Fatah Palembang. Completing a thesis is often a stressful academic challenge, potentially affecting students' mental health. To help students manage their stress and negative thoughts, this study introduces motivational content on Instagram Reels as part of the SIT intervention. The study aims to: (1) assess students' stress levels before using the SIT technique, (2) assess stress levels after the intervention, and (3) evaluate the effectiveness of the SIT technique assisted by Instagram Reels in reducing stress. Using a quantitative, descriptive approach, the study sampled 56 students from a population of 130.  he data collection technique in this study used documentation and questionnaires with a total of 25 statements for the variable (y) which had been tested for validity rcount> rtable with a range of rcount values of 0.521-0.871 and rtable 0.3415. The data analysis technique uses the wilxocon test. The results showed that the known significance value for 0.000 <0.05, so it can be concluded that the hypothesis in this study is accepted. This means that there is a significant influence, meaning that the Stress Inoculation Training (SIT) technique has a significant influence on student resilience.